2019
DOI: 10.1021/jacs.8b13653
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Effects on Indacenodithienothiophene Acceptor Packing and Electronic Structure, End-Group Redistribution, and Solar Cell Photovoltaic Response

Abstract: Indacenodithienothiophene (IDTT)-based postfullerene electron acceptors, such as ITIC (2,2′-[[6,6,12,12-tetrakis­(4-hexylphenyl)-6,12-dihydrodithieno­[2,3-d:2′,3′-d′]-s-indaceno­[1,2-b:5,6-b′]­dithiophene-2,8-diyl]-bis­[methylidyne­(3-oxo-1H-indene-2,1­(3H)-diylidene)]]­bis­[propanedinitrile]), have become synonymous with high power conversion efficiencies (PCEs) in bulk heterojunction (BHJ) polymer solar cells (PSCs). Here we systematically investigate the influence of end-group fluorination density and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
371
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(393 citation statements)
references
References 109 publications
(223 reference statements)
20
371
0
2
Order By: Relevance
“…The blend films processed with additives showed the same trend as those of Y6 pure films. The main absorption peak of GCl‐processed blend film showed a redshift from 812 to 819 nm, and became broader compared with those processed with CN, probably arising from the improved stacking of Y6 molecules . The driving force behind this could be ascribed to the heterogeneous nucleation induced by GCl.…”
Section: Detailed Photovoltaic Parameters Of Devices Employing Pm6:y6mentioning
confidence: 95%
“…The blend films processed with additives showed the same trend as those of Y6 pure films. The main absorption peak of GCl‐processed blend film showed a redshift from 812 to 819 nm, and became broader compared with those processed with CN, probably arising from the improved stacking of Y6 molecules . The driving force behind this could be ascribed to the heterogeneous nucleation induced by GCl.…”
Section: Detailed Photovoltaic Parameters Of Devices Employing Pm6:y6mentioning
confidence: 95%
“…Recently, both MD simulations and single‐crystal diffraction analyses have shown that the ITIC and IT‐4F molecules are inclined to interact with each other by end‐group π−π stacking due to the large steric hindrance of the four alkyl phenyl groups pended on the central unit. [ 5557 ] As the TDM directions of ITIC and IT‐4F are along their long molecular axes, the end‐group π−π stacking can form J‐type or V‐type dimers in the films. For the “C‐like” Y6, the TDM direction is perpendicular to its symmetrical axis, and the favorable J‐type and V‐type dimers can also form through such stacking mode in the film.…”
Section: Figurementioning
confidence: 99%
“…Despite the success of superior photovoltaic performance in nonfullerene OSCs, it is highly desired that the continued progress and improvement will be acquired in the organic photovoltaic (OPV) field, thereby accelerating the process of commercialization. In a standpoint of molecular design, halogenation is currently the extremely promising new strategy to further enhance device efficiency, which mainly concentrates on the modulation of π electron properties deriving from the strong electronegativity of halogen elements . Among all halogen group elements, fluorination and chlorination are the most extensive and effective material modification approaches and present their respective unique superiorities, including lowering the energy levels, regulating molecular packing, improving the intramolecular charge transfer (ICT) effects, and so forth.…”
Section: Introductionmentioning
confidence: 99%